AI in the Classroom: An Educational Enigma - Bradley, Jon; Allison, Sam (Apprendre et enseigner aujourd’hui, 2023)
These two opening quotations highlight the emerging dilemma faced by classroom practitioners at all levels throughout the education structure. At base, will AI turn out to be a minor irritant with relatively manageable education consequences or, on the other hand, is AI a major game changer that will fundamentally alter the overall educative process ? In the following prefatory ‘think piece’, we focus specifically on what has been identified as the most invasive conundrums that will impact all levels of society including, but not exclusively, public school classrooms. Realistically, the issue of AI is spacious with possible fundamental implications for all learners and teachers. Further, concerns may yet to be identified and unintended consequences, both positive and negative, will no doubt emerge. Nonetheless, a review of the existing shifting research literature base has identified several broad areas of concern.